2017
DOI: 10.18488/journal.aefr/2017.7.2/102.2.152.163
|View full text |Cite
|
Sign up to set email alerts
|

Finance-Growth Nexus in Bangladesh? An Empirical Analysis

Abstract: We examine the empirical relationship between financial and economic growth in Bangladesh over the period of 1985-2014 Contribution/ OriginalityThis contribution of this study is to investigate the relationship between financial development and economic growth nexus in Bangladesh by considering a new set of financial indicators. This study reveals the reasons behind a weak financial system in Bangladesh which has of great relevance for policy matters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
(13 reference statements)
1
11
0
Order By: Relevance
“…Based on bounds testing results, models 1 and 2 tend to be the long-term driving factors in determining the economic growth of Bangladesh. The findings are consistent with those of Bist and Bista [9] of Nepal, R. Pradhan [24] of India, and Amin and Hossain [10] of Bangladesh, which are from the same subcontinent. The results are also in line with Christopoulos and Tsionas [35] of Nigeria, which has a comparable degree of economic development to Bangladesh.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Based on bounds testing results, models 1 and 2 tend to be the long-term driving factors in determining the economic growth of Bangladesh. The findings are consistent with those of Bist and Bista [9] of Nepal, R. Pradhan [24] of India, and Amin and Hossain [10] of Bangladesh, which are from the same subcontinent. The results are also in line with Christopoulos and Tsionas [35] of Nigeria, which has a comparable degree of economic development to Bangladesh.…”
Section: Resultssupporting
confidence: 89%
“…Private sector loans transmit additional funds into the financial system, increasing private sector investment and stimulating economic activity within a country. Several Bangladeshi studies, including those by Amin and Hossain [10], Hasan and Barua [21], and M. H. Rahman [41], agree with this outcome. In model 2 of Table 4, the empirical findings show that a 1% increase in M2 results in a 0.0859% growth in real GDP, suggesting that broad money supply has a positive impact on economic growth.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The Granger causality test is used to check whether the time series variables provide meaningful insights (Amin and Hossain, 2017). Granger (1969Granger ( , 1980Granger ( , 1988) introduced Granger causality, and it has been widely used in empirical literature to check the causation of the variables.…”
Section: Granger Causalitymentioning
confidence: 99%
“…Schumpeter (1911) argued that technological innovation could happen if financial market works efficiently which in turn stimulates economic growth. It is evident that there exist a long run relationship between financial development and economic growth in Bangladesh (Amin and Hossain, 2017). They also identified that weak financial structure is the reason for slow economic growth, and they suggested improving financial structure through proper policy.…”
Section: Introductionmentioning
confidence: 99%